A Case of Severe Anemia in Pregnancy Treated With Traditional Chinese Medicine - Suqin Zhong; Ting Xie (Clinical Case Reports)
ABSTRACT This case report describes the treatment of a 29‐year‐old pregnant woman with severe anemia using traditional Chinese medicine (TCM). The patient, at 5 weeks of gestation, presented with a hemoglobin level of 75 g/L and had a history of autoimmune hemolytic anemia and alpha‐thalassemia, which had previously led to pregnancy termination at 17 weeks. In this case, TCM was administered with a therapeutic focus on nourishing Qi and blood, tonifying the kidneys, and supporting gestational maintenance. The patient's anemia persisted throughout gestation, with fluctuating hemoglobin levels that ultimately measured 77 g/L at delivery. Despite sustained anemia and the absence of blood transfusion, the pregnancy proceeded without major complications and resulted in the full‐term birth of a healthy infant weighing 2350 g.